Potential of Chemically Synthesized Oligosaccharides To Define the Carbohydrate Moieties of the Fungal Cell Wall Responsible for the Human Immune Response, Using Aspergillus fumigatus Galactomannan as a Model - Sarah Sze Wah Wong (American Society for Microbiology, 2020)
ABSTRACT Methodologies to identify epitopes or ligands of the fungal cell wall polysaccharides influencing the immune response of human pathogens have to date been imperfect. Using the galactomannan (GM) of Aspergillus fumigatus as a model, we have shown that synthetic oligosaccharides of distinct structures representing key fragments of cell wall polysaccharides are the most precise tools to study the serological and immunomodulatory properties of a fungal polysaccharide.